Total Kolektomi pada Adenomatous Poliposis Kolon Ganas - KASTOMO, DUKUT RESPATI (Indonesian Journal of Cancer, 2010)
Polyp hyperplasia is a neoplastic lession, abnormal gen hidding beyond the cell and developed to be malignant. Most of lession founded in rectum and sigmoid, and almost multiple, the smaller size 2 mm, appearance like a normal mucous colour and a little pale. Proportion in male and female is 13 : 1, most often in boy under 10 year-old (about four year-old), in adult around 18 year-old. Endoscopicaly incidens non adenomatous 15% - 86% under five mm in size, but 97% is adenoma if the size more than one cm. Familial Adenomatous Polyposis (FAP) 100% is became a malignancy.